A Novel 2-Carbon-Linked Dimeric Artemisinin With Potent Antileukemic Activity and Favorable Pharmacology - Kagan, Amanda B.; Moses, Blake S.; Mott, Bryan T.; Rai, Ganesha; Anders, Nicole M.; Rudek, Michelle A.; Civin, Curt I. (Frontiers in Oncology, 2022)
Acute myeloid leukemia (AML) remains a devastating disease, with low cure rates despite intensive standard chemotherapy regimens. In the past decade, targeted antileukemic drugs have emerged from research efforts. Nevertheless, targeted therapies are often effective for only a subset of patients whose leukemias harbor a distinct mutational or gene expression profile and provide only transient antileukemic responses as monotherapies. We previously presented single agent and combination preclinical data for a novel 3-carbon-linked artemisinin-derived dimer (3C-ART), diphenylphosphate analog 838 (ART838), that indicates a promising approach to treat AML, given its demonstrated synergy with targeted antileukemic drugs and large therapeutic window. We now report new data from our initial evaluation of a structurally distinct class of 2-carbon-linked dimeric artemisinin-derived analogs (2C-ARTs) with prior documented in vivo antimalarial activity. These 2C-ARTs have antileukemic activity at low (nM) concentrations, have similar cooperativity with other antineoplastic drugs and comparable physicochemical properties to ART838, and provide a viable path to clinical development.